PENGARUH ENERGI AKTIVASI TERHADAP AKTIVITAS NANOPARTIKEL ZnFe2O4 PADA ADVANCED OXIDATION PROCESSES (AOPs) SEBAGAI PENGURAI RHODAMINE B - Kadarisman, Kadarisman; Nurhasanah, Iis (BERKALA FISIKA, 2021)
Advanced  Oxidation  Processes  (AOPs)  is  one  of  the  methods  used  to  treat  organic  dye  waste. Powder-based  AOPs  as  photocatalyst  have  disadvantages  due  to  surface  adsorption  and agglomeration, thereby reducing the percentage of dye decomposition. In this study, the addition of  chemical  energy  (photo-Fenton-like)  and  ultrasonic  waves  (sono-photocatalyst)  in  the photocatalyst process was used to increase the activity of powder-based photocatalyst material as a  decomposer  of  Rhodamine  B  organic  dye.  The  photocatalyst  material  used  was  ZnFe2O4 nanoparticles synthesized using precipitation method with a calcination temperature of 700oC for 3 hours. The combination of light energy (4.69 eV) and chemical energy (44 meV) in the photo- Fenton-like process showed the highest percentage of Rhodamine B decomposition (70%). The use of  ultrasonic  energy  (28  meV)  in  the  sono-photocatalyst  process  increases  the  rate  of decomposition  of  RhB  by  2  times.  The  addition  of  chemical  energy  (44  meV)  increased  the photocatalyst activity of ZnFe2O4 nanoparticles on decomposition of RhB by 8 times. The results showed that the addition of chemical energy to the photocatalyst  activity of ZnFe2O4 was much more efficient than the addition of ultrasonic energy.